2021
DOI: 10.1111/mmi.14681
|View full text |Cite
|
Sign up to set email alerts
|

Significance of fucose in intestinal health and disease

Abstract: The deoxyhexose sugar L‐fucose is important for many biological processes within the human body and the associated microbiota. This carbohydrate is abundant in host gut mucosal surfaces, numerous microbial cell surface structures, and some dietary carbohydrates. Fucosylated oligosaccharides facilitate the establishment of a healthy microbiota and provide protection from infection. However, there are instances where pathogens can also exploit these fucosylated structures to cause infection. Furthermore, deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 83 publications
0
30
0
Order By: Relevance
“…Oligo- and polysaccharides are substances widely investigated as microbiota modulators [ 45 ]. In particular, fucose-containing saccharides are under consideration [ 46 ]. Fucose is a monosaccharide abundant in the intestinal glycoproteins, including mucin2 [ 47 , 48 ], it is presented in the terminal position of mucin2 polysaccharide chains, thus it is available to bacteria in the gut lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Oligo- and polysaccharides are substances widely investigated as microbiota modulators [ 45 ]. In particular, fucose-containing saccharides are under consideration [ 46 ]. Fucose is a monosaccharide abundant in the intestinal glycoproteins, including mucin2 [ 47 , 48 ], it is presented in the terminal position of mucin2 polysaccharide chains, thus it is available to bacteria in the gut lumen.…”
Section: Introductionmentioning
confidence: 99%
“…The T. forsythia O -glycan contains two Fuc residues, of which only the galactose-bound, inner Fuc is affected in the Δ Tanf_01305 mutant ( Figure 8 ), as previously demonstrated by detailed MS 2 analyses of that mutant [ 9 ]. Based on the loss of fucosylation in a B. fragilis mutant deficient in GDP- l -Fuc biosynthesis [ 15 ] and the demonstrated functional homology of the FucTs from B. fragilis and T. forsythia , we reasoned that the Fuc residue branching from the protein-linked Gal of the T. forsythia glycan is l -Fuc, and the GlcA-linked Fuc at the branching point of the glycan is d -Fuc. To confirm this, we created a T. forsythia Δ Tanf_07535 mutant defective in the GDP- l -Fuc synthase Fcl, which catalyzes the conversion of GDP- d -Man to GDP- l -Fuc [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of fucose (Fuc) residues in carbohydrate structures is crucial for many biological and pathological processes in both eukaryotic and prokaryotic organisms. Fucosylated bacterial oligosaccharides have been suggested to be involved in molecular mimicry, adhesion, colonization, and modulation of immune responses [ 13 , 14 , 15 ]. Previous studies have shown that both the CPSs and O -glycans of Bacteroidales contain Fuc [ 7 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Bacteroides spp. [66]. Therefore, the increased serum concentrations of fucose, fructose, and glycose might be attributed to an antibiotic-induced reduction of beneficial microbial species with the ability to ferment monosaccharides.…”
Section: Discussionmentioning
confidence: 99%